Crystallization and melting of Poly(4-hydroxybutyrate) characterized by fast scanning calorimetry - Xiangyan Yang; Runyu Zhou; Zixiao Xu; Jing Deng; Chuyue Wei; Jiahui Luo; Haoqi Luo; Lijia Zou; Yang Wu; Xin Ao; Shuaishuai Yuan; Weihua Zhou (Polymer Testing)
Poly (4-hydroxybutyrate) (P4HB) is a marine biodegradable polyester with promising applications. Unfortunately, the crystallization and melting behavior of P4HB has not been systematically studied, due to the rapid crystallization near room temperature. In particular, the characterization of crystallization and melting of P4HB by fast scanning calorimetry (FSC) has not been reported previously. In this article, the common differential scanning calorimeter (DSC), polarized optical microscopy (POM), atomic force microscopy (AFM) and FSC were performed to investigate the crystallization and melting behavior of P4HB. The results indicated that melt crystallization facilitated the formation of fragmented crystals rather than complete spherulites. Furthermore, the P4HB exhibited a broad crystallization temperature range from −19 °C to 49 °C, and the crystallization and melting of P4HB was notably affected by the temperature, in addition to the heating or cooling rates. The higher crystallization temperature and lower cooling rates facilitated the formation of well-developed crystals. Remarkably, the P4HB is found to be unable to crystallize at heating or cooling rates exceeding 6 K/s. Moreover, double melting peaks could be discerned at moderate isothermal crystallization temperature exhibiting faster crystallization rate. The findings will provide theoretical guidance on how to optimize the processing parameters in modulating the crystallization of P4HB.